Implementasi E-Katalog IKM Berbasis Website Pada Dinnakerind Di Kabupaten Demak - Nafisah, ‘Ainun; Dharmawan, Alexander; Galih, Sinta Tridian (INTECOMS: Journal of Information Technology and Computer Science, 2024)
In this digital era, information technology is very important to develop small and medium industries (SMEs). The Department of Labor and Industry of Demak Regency seeks to improve the competitiveness of SMEs through a website-based e-catalog. The aim of this research is to create and implement an e-ICM catalogue that can be accessed online by the public as well as to evaluate how effective the catalogue is in promoting local products. Needs analysis, system design, implementation, and testing are the measures used in this research. This research aims to design and implement an SMEs e-catalog that can be accessed online by the community, and evaluate its effectiveness in promoting local products. The research method includes needs analysis, system design, implementation, and testing. The result is an e-catalog website that displays complete information about SMEs products in Demak Regency, including product descriptions, images, and manufacturer contacts. This website also has a search feature and product categories to facilitate users. Using the black-box testing method, the test was conducted with a usability survey of 22 respondents, which yielded a score of 86.8%. It is expected that the system will help develop small and medium-sized industries (SMEs) in Demak district, improve product visibility, and support the local economy.